The immunological and genetic basis of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: This article presents a comprehensive review of the immunodysregulation, polyendocrinopathy, enteropathy and X-linked (IPEX) syndrome, covering both the clinical and molecular aspects of the disease. Recent findings: The IPEX syndrome is a rare immunological disorder in humans caused by inheritable mutations in the FOXP3 gene, the master transcriptional regulator for the development and function of CD4 + regulatory T (Treg) cells. Forkhead box protein 3 (FOXP3 + ) Treg cells represent a unique T-cell lineage with inhibitory functions, and are responsible for immune homeostasis and tolerance to self and nonself antigens. Evidence shows that a Treg developmental deficiency or dysfunction underlies the severe, multiorgan, autoimmune disease of IPEX. Summary: An in-depth structural and functional analysis of the molecular domains of FOXP3 is essential for our understanding of the observed clinical heterogeneity and prognosis in IPEX.